THE PHENOMENOM OF HOMELESSNESS BEGGARS AND VAGRANT IN MEDAN CITY - Ivan Santono M. T. Hutapea; Yogi Pasca Pratama (MESP–FEB UNS, 2019)
The purpose of this study are to find how the homelessness can survive in tough economy and what are the reason for being homeless. This type of research is qualitative descriptive, using the phenomenological approach method through observation techniques, and interviews. Data sources used are primary data sourced from direct observation to the location of the study by observation and interview. While other sources are documentation when conducting interviews. This study uses data from interviews with homeless people on the streets to get more real results. Data retrieval is carried out in the city of Medan especially on Nibung and Darussalam streets. The results of this study indicate that poverty is one of the most important factors that makes them choose to live as homeless people. And another factor that makes homeless people survive in the Nibung and Darussalam areas is the number of people who often share food in the area. And there are various reason that cause a person to become homelessness, such education, age, termination of employment poverty and urbanitation, etc.Keywords: Homeless, Reason to be Homelesness, Poverty